American Literature for Millennial and Centennial Undergraduates: Reflections upon an Eclectic Teaching Model - Julio Cañero Serrano (Tejuelo: Didáctica de la Lengua y la Literatura)
The question of the canon in American Literature classroom of Spanish universities is influenced by the ‘Cultural Wars’ that, since the 1990s, have been fought in the United States between the supporters of maintaining a tradition close to the dominant thought, and those that have defended the opening of the canon to obliterated voices. Starting from the definition of literary versus non-literary, this work delves into the tendencies that have determined the literary canon of the US, and those which have rejected it for its concealment of the voices of important segments of the American population (women, immigrants, and class, ethnic, racial or sexual-oriented groups). Acknowledging that today’s teachers face the challenges posed by a new generation of university students, the so-called Millennials and Centennials, who are much more receptive to the creations of the ‘Other’ -regardless of whether these creations are distinctive, by their origin or by their formal character, of what is understood as literary,- we ponder upon the need to advocate an eclectic teaching approach to American artistic creations, combining the requirement to know the canonical works with the study of those pieces of work that the tradition has reviled.